Efficient preprocessing of complex geometries for CFD simulations. Issue 3 (16th March 2019) - Ali, Zaib; Tyacke, James; Watson, Rob; Tucker, Paul G.; Shahpar, Shahrokh
ABSTRACT: Preprocessing remains one the main bottlenecks in the computational fluid Dynamics simulations of flows involving complex geometries as advances in the algorithm development, turbulence modelling and parallel computing are made. To this end, two approaches are presented here to efficiently deal with complex geometries in order to reduce the preprocessing time and manual effort. First, a hybrid blocking approach, combining the medial axis-based method with level set iso-surface is presented to aid the block topology generation for subsequent structured meshing of complex 3D external flow domains. Secondly, a hierarchical geometry handling approach is demonstrated which makes use of the lower order modelling, overset meshes and zonal blocking for efficient preprocessing. Typical external aerodynamics cases have been showcased to describe how such techniques can be used to address modern challenges in the preparation of complex geometries for flow simulations.